Analisa Perbandingan Kekuatan Bending Material Plat Kapal HLB4P004 Dengan ASTM A36 Menggunakan Variasi Kuat Arus - Kurniawati Oktarina; Agnes Dian Mahesti (LPPM Politeknik Jambi, 2022)
Ship steel plate is the main ingredient in ship building. Therefore, ship steel plate manufacturers continue to innovate to create quality steel plates for ship building in order to provide the best quality for every ship production. Quality of Material Strength Plate can be done with several tests, including bending test. Bending testing is one of the mechanical properties testing. The specimen in the form of Cargo HLB 4P004 ship plate is cut with a length of 150 mm, width 30 mm and cut into 2 parts. with welding amperes 100A, 120A and 140A then the specimens are formed with a size of 150 mm x 10 mm for later bending and the results are compared with ASTM A36 specimens. 120 Amperes with a bending strength of 0,83636434 kN /mm2, different from the ASTM A36 plate, the best bending quality obtained from a 140 Ampere welding specimen with a bending strength of 1,76107649 kN /mm2, of course material factors, welding, and plate thickness greatly affect the results of this testing.